2016
DOI: 10.1002/adfm.201601347
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Piezoelectric Energy Harvesters Utilizing (001) Textured Bimorph PZT Films on Flexible Metal Foils

Abstract: wileyonlinelibrary.comdensity and reduced resonance frequency have been explored, including advanced mechanical design, [ 5 ] maximizing intrinsic piezoelectric materials properties, [ 6,7 ] and using a fl exible passive layer. [ 8,9 ] In the last decade, microelectromechanical (MEMS) energy harvesters based on piezoelectric materials such as AlN and Pb(Zr,Ti)O 3 (PZT) have been studied for use in harvesting energy from small amplitude, mechanical vibration. [10][11][12] Improving the piezoelectric material fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(75 citation statements)
references
References 41 publications
0
67
0
1
Order By: Relevance
“…(55) We have fabricated a B-PEH based on bulk PZT thick films with a low resonant frequency over a wide range of acceleration, which was realized by utilizing low-temperature bonding and thinning technology on flexible beryllium bronze substrates at a low cost. (56) Figure 6(a) illustrates the threedimensional structure and micromachining process of B-PEH.…”
Section: Bimorph Pehs (B-pehs)mentioning
confidence: 99%
“…(55) We have fabricated a B-PEH based on bulk PZT thick films with a low resonant frequency over a wide range of acceleration, which was realized by utilizing low-temperature bonding and thinning technology on flexible beryllium bronze substrates at a low cost. (56) Figure 6(a) illustrates the threedimensional structure and micromachining process of B-PEH.…”
Section: Bimorph Pehs (B-pehs)mentioning
confidence: 99%
“…Cho et al (2016) designed a piezoelectric energy acquisition system with magnetic oscillations that harvested inertial energy and vibrational energy [12]. Yeo et al (2016) studied the PCM energy collector of the double crystal Pb (Zr, Ti)O-3 (PZT) film on the Ni foil deposited by rf magnetron sputtering [13]. Hsu et al suggested a locally amplified strain sensor based on the piezoelectric polymer [14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Moreover, flexible energy harvesters (nanogenerators) can be easily fabricated using piezoelectric materials, and they are prospective candidates for realizing self-powered flexible electronics. [11][12][13][14] In that pursuit, many researchers have demonstrated high-performance flexible energy harvesters using representative lead-based piezoelectric materials, e.g., Pb(Zr,Ti)O 3 (PZT), 11,12,14,15 even for wearable/bioimplantable applications. [16][17][18][19][20] Although the lead-based materials have excellent piezoelectric properties, they should not be utilized in ecological/biological applications due to their toxicity, a legacy of the acknowledged Pb-related poisoning.…”
mentioning
confidence: 99%